Aplicativo TopWorksheets como recurso digital didáctico, para el aprendizaje de Bioquímica con estudiantes de séptimo semestre de la carrera de Pedagogía de las Ciencias Experimentales Química y Biología - Chicaiza Uquillas, Maria Jose (2025)
The increasing incorporation of digital technologies and the challenges faced in learning biochemistry offer new opportunities in education to improve the teaching and learning of experimental sciences. This research aimed to determine the impact of interactive worksheets created with TopWorksheets on the learning of biochemistry among seventh-semester students of the Pedagogy of Experimental Sciences in Chemistry and Biology program. To this end, the work was guided by a mixed, pre-experimental, pretest-posttest approach. The sample consisted of 18 students who were given knowledge tests to determine changes in learning and a survey to determine their opinions regarding this learning strategy. The results show that comparative evaluations before and after the intervention revealed statistically significant differences: the pretest scores (M = 7.31) were lower than the posttest scores (M = 8.14), providing evidence that interactive worksheets created with TopWorksheets significantly influence biochemistry learning. This is reflected in the fact that 94.4% of students achieved the learning objectives, 72.2% perceived that the worksheets helped reinforce their understanding of the topics, and 88.9% considered that the interactive worksheets increased their participation in Biochemistry classes. In conclusion, the integration of TopWorksheets proved effective in improving biochemistry learning and student motivation, underscoring the importance of using interactive digital tools in science teaching.